If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -3y + 4 = 0 Reorder the terms: 4 + 2x + -3y = 0 Solving 4 + 2x + -3y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + 2x + -4 + -3y = 0 + -4 Reorder the terms: 4 + -4 + 2x + -3y = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 2x + -3y = 0 + -4 2x + -3y = 0 + -4 Combine like terms: 0 + -4 = -4 2x + -3y = -4 Add '3y' to each side of the equation. 2x + -3y + 3y = -4 + 3y Combine like terms: -3y + 3y = 0 2x + 0 = -4 + 3y 2x = -4 + 3y Divide each side by '2'. x = -2 + 1.5y Simplifying x = -2 + 1.5y
| 12x-5y=0 | | 10x+8=5x+128 | | 89-2x=3x+24 | | 160-7x=20x+19 | | 5x+6=-84-10x | | y=3(5)+23 | | 4x+31=12x-49 | | 7y-12=9 | | 4r+6=22 | | e-15=16 | | 6t=42 | | w-9=5 | | 11x+12=6x+102 | | h+7=15 | | 105-2x=25x+18 | | 12-9x=67-44x | | (n+4)x*4=48 | | 94-2x=43x-19 | | 126-5x=5x+6 | | 6a-6=42 | | 125-3x=5x+21 | | 237-3x=42x+22 | | 3n=12 | | 3x+2=18-5x | | x+8=3+2x | | 5x+13=-39-8x | | 114-2x=9x+18 | | 4x+7y=299 | | 16x-8=6x+42 | | 13x+13=76-4x | | 34-g=25 | | 18x-9=6x+42 |